2021
DOI: 10.3390/cancers13205182
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Gene Signature for Squamous Cell Carcinoma with a Higher Risk for Treatment Failure and Accelerated MEK-ERK Pathway Activity

Abstract: Squamous cell carcinoma (SCC) is the most prevalent histological type of human cancer, including head and neck squamous cell carcinoma (HNSCC). However, reliable prognostic gene signatures for SCC and underlying genetic and/or epigenetic principles are still unclear. We identified 37 prognostic candidate genes by best cutoff computation based on survival in a pan-SCC cohort (n = 1334) of The Cancer Genome Atlas (TCGA), whose expression stratified not only the pan-SCC cohort but also independent HNSCC validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…18 In HNSC, COL5A1 has been identified as one of the key nodes in a regulatory work correlating with prognostic phenotype. 19 Moreover, it has been defined as a hub gene linking to perineural invasion, a key pathological characteristic of HNSC predicting poor survival. 20 Likewise, the upregulation and the potential involvement of COL5A1 in tumorigenesis was found in OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In HNSC, COL5A1 has been identified as one of the key nodes in a regulatory work correlating with prognostic phenotype. 19 Moreover, it has been defined as a hub gene linking to perineural invasion, a key pathological characteristic of HNSC predicting poor survival. 20 Likewise, the upregulation and the potential involvement of COL5A1 in tumorigenesis was found in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of COL5A1 has been found in multiple human solid tumors and affected spanning cellular behaviors, such as proliferation and motility and linked to immunosuppression 18 . In HNSC, COL5A1 has been identified as one of the key nodes in a regulatory work correlating with prognostic phenotype 19 . Moreover, it has been defined as a hub gene linking to perineural invasion, a key pathological characteristic of HNSC predicting poor survival 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It is highly expressed in papillary thyroid carcinoma, and silencing of FBN1 inhibits cell viability and colony formation in vitro and inhibits tumor growth in vivo ( Ma et al, 2016 ). In addition, FBN1 is also a key gene associated with the prognosis of squamous cell carcinoma through a comprehensive analysis of multi-omics data ( Feng et al, 2021 ). In renal clear cell carcinoma, microarray analysis reveals that FBN1 induction is accompanied by a higher malignancy grade and progression.…”
Section: Role Of Fbn1 In Tumorigenesismentioning
confidence: 99%
“…Trametinib has been approved for the treatment of melanoma, non‐small cell lung cancer, and thyroid cancer patients harboring the BRAF V600E mutation [14–16]. In line with the prediction that it would be effective in the treatment of high‐risk HNSCC [17], trametinib was tested in a phase II neoadjuvant window‐of‐opportunity clinical trial—with promising results [18]. However, a follow‐up study showed that tumors developed resistance to trametinib monotherapy via upregulation of yes‐associated protein 1 (YAP1) [19].…”
Section: Introductionmentioning
confidence: 99%